INTEGRATING TNFD INTO GREEN FINANCE TO SUPPORT AN INCLUSIVE AND SUSTAINABLE ECONOMIC TRANSFORMATION IN SUMATRA - Khulsum, Umi; Utami, Pertiwi; Risna, Meilia; Zuhriyah, Nur azizah; Muzammil, Rozina (LP2M IBK Nitro, 2025)
This study analyzes the potential implementation of the Taskforce on Nature-related Financial Disclosures (TNFD) to strengthen green finance and sustainable economic transformation in Sumatra. The research background includes the global economic crisis, post-pandemic recovery gaps, and the need for transparency in Green Finance. This study uses a qualitative approach and policy review based on secondary data from Bank Indonesia, Statistics Indonesia (BPS), the Ministry of Finance, the Financial Services Authority (OJK), and TNFD documents. The results show that the success of TNFD implementation in Sumatra is strongly influenced by the synergy of monetary, fiscal, and macroprudential policies as well as the readiness of financial institutions to adopt nature risk disclosure. Strategic sectors such as food, renewable energy, and downstreaming have significant potential to become models for TNFD implementation through digital reporting. This study recommends the development of a TNFD integration roadmap, strengthening of the national data center, and green finance incentives to attract green investment. These findings contribute to the green finance literature and provide policy implications for inclusive and sustainable economic growth in the region.